Mitochondrial membrane depolarization enhances TRAIL-induced cell death in adult human granulosa tumor cells, KGN, through inhibition of BIRC5 - Julie A. MacDonald; Niharika Kura; Carleigh Sussman; Dori C. Woods (BMC, 2018)
Abstract Background Cellular metabolic changes that accompany malignant transformation have been heralded as hallmark features of cancer. However, metabolic signatures between neoplasms can be unique, allowing for distinctions in malignancy, invasion and chemoresistance between cancer types and subtypes. Mitochondria are central metabolic mediators, as cellular bioenergetics veers from oxidative phosphorylation to glycolysis. Herein, we evaluate the role of mitochondria in maintenance of cellular metabolism, proliferation, and survival in the adult granulosa tumor cell line, KGN, as well as three epithelial ovarian cancer cell lines to determine distinctions in specific features. Results Notably, KGN cells were susceptible to TRAIL- and cisplatin-induced death following pretreatment with the metabolic inhibitor FCCP, but not oligomycin A. Collapse of mitochondrial membrane potential was found concomitant with cell death via apoptosis, independent from extrinsic canonical apoptotic routes. Rather, treatment with FCCP resulted in elevated cytochrome c release from mitochondria and decreased responsiveness to BIRC5. Following knockdown of BIRC5, mitochondrial membrane depolarization further sensitized KGN cells to induction of apoptosis via TRAIL. Conclusions These results indicate an essential role, distinct from metabolism, for mitochondrial membrane potential in KGN cells to sense and respond to external mediators of apoptotic induction.